Hubungan Tingkat Pengetahuan dengan Kepatuhan Minum Obat pada Pasien TB Paru di RSUI Harapan Anda Kota Tegal - Rina Fatmawati; Herry Susanto; Kurnia Wijayanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Medication adherence among pulmonary TB patients is crucial to prevent recurrence and ensurecomplete recovery. Patient knowledge of tuberculosis treatment and adherence to prescribed dosages andadministration methods are key components to successful treatment. This study aimed to determine therelationship between knowledge and medication adherence in pulmonary TB patients at Harapan Anda IslamicHospital, Tegal City. This study used a quantitative cross-sectional design. A sample size of 60 pulmonary TBpatients at Harapan Anda Islamic Hospital, Tegal City, was selected through purposive sampling. Data werecollected using a knowledge questionnaire and a medication adherence questionnaire. Data were analyzed usingthe chi-square test. Based on the analysis results, it was found that of the 60 patients with pulmonary TB atHarapan Anda Islamic Hospital, Tegal City, most were in the early elderly age (46-55 years), most were malebecause they were men, the majority were married, most had graduated from high school and most had privateemployment status. The level of compliance with taking medication in patients with pulmonary TB at HarapanAnda Islamic Hospital, Tegal City was in the high category. There was a relationship between the level ofknowledge and compliance with taking medication in patients with pulmonary TB at Harapan Anda IslamicHospital, Tegal City. There was a relationship between the level of knowledge and compliance with takingmedication in patients with pulmonary TB at Harapan Anda Islamic Hospital, Tegal City. Patients who had goodknowledge tended to be more compliant in undergoing treatment. These results serve as input for health servicesto provide health service programs to improve knowledge and compliance with taking medication in patients withpulmonary TB better.